Longday Photoperiod Accelerates Flowering in Indonesian Non-Flowering Shallot Variety - Fazat Fairuzia; Sobir Sobir; Awang Maharijaya; Masaki Ochiai; Kunio Yamada (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The shallot flowering ability is essential to increase productivity by assembling superior varieties through the hybridization and botanical seed or true shallot seed (TSS). The photoperiod length greatly influences flowering in shallot, which plays a significant role in the flowering initiation. This research aims to study flowering responses with different photoperiods in shallots. Six shallot varieties: Lokananta, Bima Brebes, Rubaru, Palasa, Biru Lancor, and Batu Ijo, were grown in a greenhouse under a short-day photoperiod, 10 hours of natural condition photoperiod for 60 days. Furthermore, half of the plants are moved to long-day treatment. The temperature during plantation is around from 7-13°C (similar to Indonesia’s upland temperature). The results indicate that long-day photoperiod increased the shallot flowering response on the five shallot varieties tested, except Rubaru. Rubaru could not produce flowers under both photoperiod treatments 120 days after plantation (DAP). Lokananta variety is the most responsive variety to flower, even on short-day photoperiod. Palasa variety, which could not flower under Indonesian photoperiod conditions, could produce flowers on long-day treatment and underplanting conditions at low to moderate temperatures.